Taking a nuanced look at adolescent technology use and negative affect: the protective role of preparedness - McFarland, Sean; Tan, Tse Yen; De France, Kalee; Hoffmann, Jessica D. (Frontiers in Psychiatry, 2023)
Adolescents are online more than any other age group, with the majority of their time on social media. Increases in technology use among adolescents have heightened conversations regarding its effects on their negative affect. There have been mixed findings regarding the relationship between technology use and negative affect; some studies present a negative association or no association, and some show a positive association. To clarify this relationship, we propose moving away from asking only how much adolescents use technology to asking how and what they use it for. We employed the Multidimensional Healthy Technology Use and Social Media Habits Scale (MTECH) and adapted forms of the Positive and Negative Affect Schedule (PANAS) in a sample of 7,234 students to assess the extent to which students feel prepared to use technology safely and successfully and whether this impacts the association between the amount of various types of technology they use and their negative affect. We conducted eight moderated regression analyses that, in some models, revealed preparedness had a protective role in the association between technology use and negative affect. In these models, at all levels of technology use, adolescents with higher levels of preparedness experienced lower levels of negative affect than their peers; however, in some instances, this effect was diminished for those using technology with high frequency. These findings support the notion that the association between technology and negative affect is not best modeled as a direct relationship, and instead that we must consider important moderators of this complex association.